Alterations of DNA repair in melanoma cell lines resistant to cisplatin, fotemustine, or etoposide - Rünger, Thomas M.; Schadendorf, Dirk (The journal of investigative dermatology, 2000)
Resistance to chemotherapy is a common phenomenon in malignant melanoma. In order to assess the role of altered DNA repair in chemoresistant melanoma, we investigated different DNA repair pathways in one parental human melanoma line (MeWo) and in sublines of MeWo selected in vitro for drug resistance against four commonly used drugs (cisplatin, fotemustine, etoposide, and vindesine). Host cell reactivation assays with the plasmid pRSVcat were used to assess processing of different DNA lesions. With ultraviolet-irradiated plasmids, no significant differences were found, indicating a normal (nucleotide excision) repair of DNA photoproducts. With singlet oxygen-treated plasmid, the fotemustine- and cisplatin-resistant lines exhibited a significantly increased (base excision) repair of oxidative DNA damage. With fotemustine-treated plasmid, the fotemustine-resistant subline did not exhibit an increased repair of directly fotemustine-induced DNA damage. Similar results were obtained with cisplatin-induced DNA crosslinks in the cisplatin-resistant line. The fotemustine- and etoposide-resistant sublines have been shown to exhibit a reduced expression of genes involved in DNA mismatch repair. We used a ‘‘host cell microsatellite stability assay'' with the plasmid pZCA29 and found a 2.0-fold to 2.5-fold increase of microsatellite frameshift mutations (p ≤0.002) in the two resistant sublines. This indicates microsatellite instability, the hallmark of an impaired DNA mismatch repair. The increased repair of oxidative DNA damage might mediate an increased chemoresistance through an improved repair of drug-induced DNA damage. In contrast, a reduced DNA mismatch repair might confer resistance by preventing futile degradation of newly synthesized DNA opposite alkylation damage, or by an inability to detect such damage and subsequent inability to undergo DNA-damage-induced apoptosis.